EFFECT OF THE SANDS CLOSE TO THE MASCARA REGION IN THE MANUFACTURE OF SELF-COMPACTING MORTARS - L, Laoufi 1; I., Laoufi 2; A., Benazzouk3 (university of eloued جامعة الوادي, 2020)
Sand plays a very important role during the manufacture of concrete and mortar for the need of civil engineering and building. It influences both the properties of cementary materials in the fresh state and in the hardened state. The objective of this work is the development of self-compacting mortars with the various sands existing in the region of the city of Mascara for the main study of mechanical performance. Six sands were used for this purpose: three natural sands and three crushed sands. The tests carried out during this research are: physical tests, tests in the fresh state and tests on hardened mortars. The results to which our research has led is that self-compacting mortars made with crushed sands give a granular skeleton with high compactness and superior mechanical performance compared to self-compacting mortars made with natural sands.
artical
Keywords: Self-compacting mortar, Sand, Formulation.